A neuroanatomical correlate of sensorimotor recovery in response to repeated vaginocervical stimulation in rats - Komisaruk, Barry R.; Conde, Dina R. (Frontiers in Physiology, 2012)
Gentle probing against the cervix via the vagina (vaginocervical stimulation, VCS) increases tail flick latency (TFL) to radiant heat; greater force abolishes the tail flick response and other withdrawal responses. This effect occurs in spinal cord-transected rats and in intact rats. On the basis of our earlier finding that VCS releases vasoactive intestinal peptide (VIP) into the spinal cord, and others’ reports of neurotrophic effects of VIP in vitro, we hypothesized that repeated VCS would stimulate sprouting and sensorimotor function of terminals of genital nerve primary afferents in the sacral spinal cord. To test this hypothesis, in the present study, we denervated the genital tract only unilaterally, which significantly reduced the TFL-elevating effect of VCS. Then we applied repeated daily VCS for 1 week and compared the subsequent effectiveness of acute VCS in elevating TFL. The rats that received the repeated daily VCS showed a significantly greater elevation in TFL in response to acute VCS than control rats that did not receive the repeated stimulation. Then, to test whether daily repeated VCS stimulates sprouting of genital primary afferents in such unilaterally genital tract-denervated rats, we transected the contralateral remaining intact pelvic nerve, applied horseradish peroxidase (HRP) to its proximal cut end for 1–2 h, and 2–3 days later counted HRP particles in its terminal zone (L6–S1) in the spinal cord. There were significantly more HRP particles in the rats that received the daily repeated VCS than in the control rats. In the context of these findings, we conclude that VCS in rats can produce a functional sensorimotor recovery via a neurotrophic effect on compromised primary afferents in the spinal cord.